Comparison of efficacy between levonorgestrel intrauterine system and dienogest in adenomyosis: a randomized clinical trial - Satish Choudhury; Saubhagya Kumar Jena; Subarna Mitra; Biswa Mohan Padhy; Sudipta Mohakud (SAGE Publishing, 2024)
Background: Medical management of adenomyosis is an emerging perspective in modern gynecology. Though levonorgestrel intrauterine system (LNG-IUS) and dienogest (DNG) effectively relieve symptoms in adenomyosis, neither has been approved for the same indication. Our study aims to compare the efficacy and safety of these progestins in treating adenomyosis. Objective: To study the efficacy and safety of LNG-IUS versus DNG in patients with symptomatic adenomyosis. Design: Open-labeled, parallel, single-centered, randomized clinical trial. Methods: Patients with adenomyosis-associated pain with or without abnormal uterine bleeding were randomly allocated to either LNG-IUS group or DNG group. The primary outcome was a reduction in painful symptoms after 12 weeks of treatment measured by visual analog scale (VAS) score. Changes in menstrual blood loss (MBL), improvement in quality of life (QoL), and adverse drug reactions were also analyzed. Results: The VAS score significantly decreased from baseline in both groups. The baseline and post-treatment VAS scores in the LNG-IUS group were 6.41 ± 1.07 and 3.41 ± 1.04 ( p  = <0.001) and in the DNG group, were 6.41 ± 0.95 and 3.12 ± 1.40 ( p  = <0.001), respectively. A significantly greater proportion of patients in the LNG-IUS group experienced lighter MBL as compared to the DNG group [27/30 (90%) in the LNG-IUS group versus 17/22 (77.2%) in the DNG group ( p  = 0.006)]. Both the groups had improvement in QOL scores calculated by the World Heath Organisation QOL scale (WHOQOL BREF) questionnaire; however, it was more pronounced in the DNG group [(28.76 ± 30.47 in the LNG-IUS group versus 48.26 ± 44.91 in the DNG group ( p  = 0.04)]. Both the agents were safe as there were no reported major adverse drug reactions. Conclusion: DNG can be an effective and safe alternative to LNG-IUS for the medical management of adenomyosis. Trial registration: The trial was prospectively registered at the clinical trial registry - India (CTRI) vide CTRI number CTRI/2020/05/025186.